Ontogenetic development and main enzymes of the digestive system in early stages of fish (Orinoquia, 2021)
There are many factors that influence the production of larvae and fingerlings of fish, among which the temperature, the quality of the water, the species, the nutritional status, the quality and quantity of the food available during the first feeding stand out, among others. This food must support the different physiological and structural changes in the development of organs and systems. The digestive system is one of the most important during the early stages of fish, because it is where the main absorption of sufficient nutrients for growth and development occurs. However, there are differences in development between species, thus considering the ontogenetic study of the digestive tract a useful tool to determine the opportune moment for the formation of the different organs. In this sense, knowing and understanding the management of the first feeding and how it influences the development of the digestive system of larvae is a fundamental aspect that influences the success of the production of quality and resistance larvae. Therefore, the objective of this review is to offer updated information on the ontogenetic development and main enzymes of the digestive system, as well as the influence of the type of food on the development of fish larvae.
Keywords: Organogenesis; digestive enzymes; cladocerans; dry diets